Limity antropologie dětství: Případ „dětství“ v sociálně vyloučené lokalitě - Fatková, Gabriela (Lidé města, 2013)
The aim of this study is to acquaint Czech readers with an often unmentioned sub-discipline of anthropology. This case study of "childhood" in the situation of social exclusion should open discussion on the epistemological barriers that the fieldworker faces when he wants an insight into the child's emic perspective. The main question that the study focuses on is how "childhood" is conceptualised in socially excluded localities. We will try to show a de-essentialised look at childhood as a phenomenon and its clash with the educational system. We will analyse socially excluded "childhood" using Berger's and Luckman's concept of social constructivism and Granovetter's concept of strong and weak ties. The result will be linked with pedagogical discourse, which, until now, entirely formed the way of thinking about children and childhood.